Emotional Stimuli on Intellect Among Older Adults from Islamic Psychospiritual Perspective - Sa'ari, Che Zarrina; Sa'ari, Nurul Salikin; Syed Abdul Rahman, Syed Mohammad Hilmi; Che Nordin, Mohd Khairul Naim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2019)
The article discusses impact of emotional stimuli on older adults’ intellect from Islamic psychospiritual perspective. The study elaborates intellect, emotion and emotional stimuli types with focuses on three stimulus that are sensory organ (hiss), cognitive or mind (ʽaql) and heart (qalb). It is suggested the positive emotional stimuli to be applied on older adult to enhance their attention and emotion. In collecting data, the study employs the method of literature review and uses the descriptive analysis in analysing data. The finding shows the positive emotional stimuli types comprising seeing the signs of Allah’s powerful, hearing good things, memorising and understanding the Quranic verses and reciting the dhikrullah and prayers will have impact on older adults’ intellect. It suggests that the more often older adults visualise, listen, memorise and recite the suggested positive emotional stimuli, the stronger their memory becomes. They also appear to have a peace and happy mind, tranquillity and satisfaction.